Determinación coproparasitológica en animales reservorios de parásitos intestinales humanos, como riesgo de transmisión. Chimborazo, 2019 - Cristian Joao, Vázquez Taza (2019)
Anthropozoonotic parasites, are those that are transmitted from the animal to the human, represent a significant risk for people who maintain contact with them, pets and animals reared in the peridomycile are epidemiologically important. The study was of a quantitative approach, with a non-experimental methodological design - transversal and with a descriptive - exploratory scope. The objective of the investigation was to detect enteroparasites in animals from the community of San Andrés, province of Chimborazo. For which, three coproparasitological techniques were used: Direct Exam, Ritchie and Ziehl-Neelsen. The feces of 300 animals were analyzed: 104 herbivores, 26 omnivores, 85 carnivores, 24 leporids, 48 rodents, 13 birds. The majority were 90.3% parasitized (X2=390,427 P<0.0001), the species detected were: Blastocystis sp., Entamoeba sp., E. bovis, E. polecki, E. coli, E. histolytica/E. dispar, E. hartmanni, Endolimax nana, Iodamoeba butschlii, Giardia sp., Enteromonas hominis, Retortamonas intestinalis, Chilomastix mesnili, Balantidium coli, Cryptosporidium sp., Eimeria sp., Ascaris sp., A. caninum, Echinoccus granulosus. There was a greater infection by protozoa 262/300 (87.3%) than by helminths 93/300 (31.0%) (X2=197.029 P<0.0001). Cows, sheep and guinea pigs were the most parasitized (100%) (X2=50,789 P<0.0001). There were no significant differences between domestic and peridomestic. These results prove that animals from the community of San Andrés act as reservoirs of human enteroparasites, being an important source of infection for residents. As control measures, health education is considered, veterinary control being indispensable, where it includes antiparasitic treatment.